Historical aspects of co-authorship networks in a Latin American journal of natural sciences: Caldasia 1940-2021: - Restrepo-Arango, Cristina (2023)
Objective: to analyze the scientific structure of the collaboration in the journal Caldasia throughout its history. Methods: Uses co-authoring network analysis and uses Gephi software. Results:  The network for the period from 1940 to 1995 is made up of five communities, where an author to communicate with another author requires crossing three authors to interact with other researchers, while the network for the period from 1996 to 2002 is made up of three communities; in this network an author only needs to cross two authors to interact with other authors. The network from 2003 to 2015 is made up of ten communities, in this network an author needs to cross an average of author and medium to interact with other researchers. The network for the period from 2016 to 2021 is made up of nine communities and to interact with other authors you have the same distance as the previous network to communicate. Intermediation in co-authorship networks in each of the periods shows that only 20 of 89 authors are information intermediaries. The number of articles in collaboration ranges from one to six and the conglomerates of co-authorship networks are made up of one to nine authors. Conclusions: The co-authorship networks of the four periods are not cohesive and are formed by conglomerates that respond to different research interests, or to different periods or to different institutional affiliations.